Estimating the Impact of Time-Invariant Variables on FDI with Fixed Effects - Ronald B. Davies; Delia Ionascu; Helga Kristjánsdóttir (Copenhagen Business School (CBS), Department of Economics, 2007)
This paper applies the panel fixed effects with vector decomposition estimator to three FDI datasets to estimate the impact of time-invariant variables on FDI while including fixed effects. We find that the omission of fixed effects significantly biases several of these variables, especially those proxying for trade costs and culture. After including fixed effects, we find that many time-invariant variables indicate the importance of vertical FDI. We also find that by eliminating these biases, the differences across datasets largely disappear. Thus, controversies in the literature that are driven by differences in data sets may be resolved by using this estimation technique.
hdl:10398/7610
Keywords: F14; F23; 330; Foreign Direct Investment; Trade Costs; Culture